Lost for words : a novel - St. Aubyn, Edward, 1960- (Farrar, Straus and Giroux, 2014)
Edward St. Aubyn's Patrick Melrose novels were some of the most celebrated works of fiction of the past decade. Ecstatic praise came from a wide range of admirers, from literary superstars such as Zadie Smith, Francine Prose, Jeffrey Eugenides, and Michael Chabon to pop-culture icons such as Anthony Bourdain and January Jones. Now St. Aubyn returns with a hilariously smart send-up of a certain major British literary award. The judges on the panel of the Elysian Prize for Literature must get through hundreds of submissions to find the best book of the year. Meanwhile, a host of writers are desperate for Elysian attention: the brilliant writer and serial heartbreaker Katherine Burns; the lovelorn debut novelist Sam Black; and Bunjee, convinced that his magnum opus, The Mulberry Elephant, will take the literary world by storm. Things go terribly wrong when Katherine's publisher accidentally submits a cookery book in place of her novel; one of the judges finds himself in the middle of a scandal; and Bunjee, aghast to learn his book isn't on the short list, seeks revenge. Lost for Words is a witty, fabulously entertaining satire that cuts to the quick of some of the deepest questions about the place of art in our celebrity-obsessed culture, and asks how we can ever hope to recognize real talent when everyone has an agenda"--